Chemically controlled sintering and microstructural development in ceramics - Kolar, Drago (Kovine zlitine tehnologije, 1997)
The sintering step in manufacturing most ceramic articles is diminated by the chemical reactions which occur during firing. Such chemical reactions may be caused by chemical heterogeneity of the constituents of the ceramic body, small amounts of additives or impurities. Even in chemically equilibrated multicomponent systems the capilary forces may cause dehomogenisation and influence the sintering mechanism. Reaction sintering in the ?$BaTiO_3$?-?$CaZrO_3$?-?$TiO_2$? system is described as an example of a system where controlled chemical heterogeneity may optimize the electrical properties. Sintering of ?$PbZr_{1-x}Ti_xO_3$? ceramic is described as an example of chemical dehomogenisation due to capilary forces.
Keywords: ceramic; keramika; sintranje; mikrostruktura; barijev titanat; piezokeramika